Pre-service EFL teachers' conceptions and strategy use in managing online classes. (February 2022) - Taghizadeh, Mahboubeh; Amirkhani, Sahar
Abstract: This study investigated the conceptions and strategy use of 104 pre-service EFL teachers while they were managing online English language classes at Iran University of Science and Technology (IUST). Data were collected through the use of a questionnaire on classroom management strategies and 16 questions on challenging online situations in terms of managing online teaching, content, interaction, time, and behavior. Analysis of the data revealed that time management, course organization, positive reinforcement, and building a positive atmosphere were considered the most important strategies for online classroom management. The results also showed that the student teachers mostly suggested the use of collaborative tasks and learner-centered strategies in response to the challenges of online classes. The findings suggest that teachers have a key role in building rapport as well as creating a positive, safe, and friendly atmosphere within online classes. These findings have implications for language teacher education programs to develop pre-service teachers' strategies for managing online English language classes.